Efficient capture of carbon dioxide with novel mass‐transfer intensification device using ionic liquids. Issue 8 (14th March 2013) - Zhang, Liang‐Liang; Wang, Jie‐Xin; Liu, Zhi‐Ping; Lu, Ying; Chu, Guang‐Wen; Wang, Wen‐Chuan; Chen, Jian‐Feng
Abstract : A novel mass‐transfer intensified approach for CO2 capture with ionic liquids (ILs) using rotating packed bed (RPB) reactor was presented. This new approach combined the advantages of RPB as a high mass‐transfer intensification device for viscous system and IL as a novel, environmentally benign CO2 capture media with high thermal stability and extremely low volatility. Amino‐functionalized IL (2‐hydroxyethyl)‐trimethyl‐ammonium (S)−2‐pyrrolidinecarboxylic acid salt ([Choline][Pro]) was synthesized to perform experimental examination of CO2 capture by chemical absorption. In RPB, it took only 0.2 s to reach 0.2 mol CO2 /mol IL at 293 K, indicating that RPB was kinetically favorable to absorption of CO2 in IL because of its efficient mass‐transfer intensification. The effects of operation parameters on CO2 removal efficiency and IL absorbent capacity were studied. In addition, a model based on penetration theory was proposed to explore the mechanism of gas–liquid mass transfer of ILs system in RPB. © 2013 American Institute of Chemical Engineers AIChE J, 59: 2957–2965, 2013